Methyl 3-Bromo-4,5-dihydroxybenzoate Attenuates Inflammatory Bowel Disease by Regulating TLR/NF-κB Pathways - Jing Huang; Lei Li; Liyan Xu; Lixin Feng; Yuxin Wang; Attila Gabor SIK; Meng Jin; Rongchun Wang; Kechun Liu; Xiaobin Li (Marine Drugs)
Inflammatory bowel disease (IBD) is characterized by uncontrolled, chronic relapsing inflammation in the gastrointestinal tract and has become a global healthcare problem. Here, we aimed to illustrate the anti-inflammatory activity and the underlying mechanism of methyl 3-bromo-4,5-dihydroxybenzoate (MBD), a compound derived from marine organisms, especially in IBD, using a zebrafish model. The results indicated that MBD could inhibit the inflammatory responses induced by CuSO4, tail amputation and LPS in zebrafish. Furthermore, MBD notably inhibited the intestinal migration of immune cells, enhanced the integrity of the gut mucosal barrier and improved intestinal peristalsis function in a zebrafish IBD model induced by trinitro-benzene-sulfonic acid (TNBS). In addition, MBD could inhibit ROS elevation induced by TNBS. Network pharmacology analysis, molecular docking, transcriptomics sequencing and RT-PCR were conducted to investigate the potential mechanism. The results showed that MBD could regulate the TLR/NF-κB pathways by inhibiting the mRNA expression of TNF-α, NF-κB, IL-1, IL-1β, IL6, AP1, IFNγ, IKKβ, MyD88, STAT3, TRAF1, TRAF6, NLRP3, NOD2, TLR3 and TLR4, and promoting the mRNA expression of IL4, IκBα and Bcl-2. In conclusion, these findings indicate that MBD could be a potential candidate for the treatment of IBD.